2020
DOI: 10.1029/2020ja028128
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Comparisons of Large Nighttime Magnetic Perturbation Events Relevant to GICs

Abstract: Nearly all studies of impulsive magnetic perturbation events (MPEs) with large magnetic field variability (dB/dt) that can produce dangerous geomagnetically induced currents (GICs) have used data from the Northern Hemisphere. Here we present details of four large‐amplitude MPE events (|ΔBx| > 900 nT and |dB/dt| > 10 nT/s in at least one component) observed between 2015 and 2018 in conjugate high‐latitude regions (65–80° corrected geomagnetic latitude), using magnetometer data from (1) Pangnirtung and Iqaluit i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 53 publications
1
33
1
Order By: Relevance
“…The significantly larger range in SML values for postmidnight events than for premidnight events in all three time delay categories (also shown in Figure 11) is more difficult to understand. As Engebretson et al (2020) suggested in regard to the MPEs associated with an interval of omega bands, it is possible that two separate and highly localized magnetotail-magnetosphere-ionosphere coupling mechanisms may be responsible for generating the large, rapid geomagnetic perturbations that generate premidnight and postmidnight GICs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly larger range in SML values for postmidnight events than for premidnight events in all three time delay categories (also shown in Figure 11) is more difficult to understand. As Engebretson et al (2020) suggested in regard to the MPEs associated with an interval of omega bands, it is possible that two separate and highly localized magnetotail-magnetosphere-ionosphere coupling mechanisms may be responsible for generating the large, rapid geomagnetic perturbations that generate premidnight and postmidnight GICs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The local time range of the "postmidnight" MPE population matches that of omega bands (Syrjäsuo & Donovan, 2004), which were identified along with other auroral phenomena by Akasofu and Kimball (1964) and Akasofu (1974). Engebretson et al (2020) reviewed many of the properties of omega bands, including the ionospheric currents associated with them, as part of a recent study of MPEs observed in conjugate hemispheres that included an interval of MPEs associated with omega bands, so these will not be repeated here. This study, however, pointed out that "postmidnight" MPEs exhibited even less temporal and spatial correlation between MPEs than "premidnight" MPEs, and suggested the possibility that the mesoscale mechanisms that produce MPEs in these two MLT ranges might be at least somewhat different.…”
Section: 1029/2020sw002526mentioning
confidence: 99%
“…A more recent paper (Engebretson et al., 2020) reported case studies of four intervals containing MPEs using data from magnetometers in Western Greenland and eastern Arctic Canada as well as magnetically conjugate sites in Antarctica. This paper found that conjugate premidnight MPEs were often but not always simultaneous to within 3 min over ∼100–700 km in latitude, while postmidnight MPEs associated with an omega band were very localized and independent in time.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent paper (Engebretson et al, 2020) reported case studies of four intervals containing MPEs using data from magnetometers in Western Greenland and eastern Arctic Canada as well as magnetically conjugate sites in Antarctica. This paper found that conjugate premidnight MPEs were often but not always simultaneous to within 3 min over ∼100-700 km in latitude, while postmidnight MPEs associated with an omega band were very localized and independent in time.…”
mentioning
confidence: 99%